DESIGN AND CONSTRUCTION OF INTERNET BASED MONITORING DEVICES THINGS(IOT) FOR MONITORING METHANE GAS IN MINES COAL USING MQ-4 SENSOR - Aditia Prathama; Ahmad Taqwa; Adewasti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Methane gas (CH₄) is a flammable gas and has the potential to cause an explosion if it accumulates in high concentrations. Therefore, an effective monitoring system is needed to detect the presence of methane gas to prevent the danger of gas leaks. This research aims to design and build a methane gas monitoring tool based on the MQ-4 sensor which is capable of detecting the presence of methane gas in real-time. This system uses a microcontroller as the main processing unit and is equipped with a wireless communication module for sending data to the monitoring platform. The MQ-4 sensor was chosen because of its high sensitivity to methane gas and its ability to measure gas concentrations in ppm (parts per million). Measurement data is displayed via a user interface that enables remote monitoring and provides early warning if gas levels exceed specified thresholds. Test results show that this system is able to detect methane gas with good accuracy and provides a fast response to changes in gas concentration. Thus, this tool can be used as an early warning system to improve safety in environments that are at high risk of methane gas leaks.